O Kronosach. Garbaczewski rozczytuje Gombrowicza - Pogonowicz, Judyta (Przestrzenie Teorii, 2023)
The article presents the performance Kronos, directed by Krzysztof Garbaczewski in 2013. The performance was an immediate reaction to the extremely intimate work of art written by Witold Gombrowicz. Garbaczewski is involved in reading and staging Gombrowicz’s work since 2008. The article highlights how the creative method presented in Kronos is portrayed by actors during the performance. Moreover, the author shows the phenomenon of poetry epiphany in the play, the coexistence of corporeality and the mind, the processes of tabooisation of the body and mediatization in the play. The author points to common points in the works of Gombrowicz and Garbaczewski. She also draws attention to how the writer’s authority is invoked, a process through which the director legitimises the theatrical exploration.